Penguatan Hukum Bisnis Untuk Mendukung UMKM di Era Digital - Ante, Rinny; Palilingan, Janesandre; M Suot , Royke (Jurnal Pendidikan Indonesia, 2025)
Existing business law regulations are still based on conventional models, so they are not fully relevant to digital dynamics. MSMEs have a strategic role in the Indonesian economy. However, the great potential of these MSMEs is often hampered by various factors, one of which is the weak legal support of businesses that can protect and empower them in the digital era. Competition between MSMEs and large companies has become increasingly sharp in this era. The problems in this study are formulated as follows: how the current non-conformity of business law regulations affects the competitiveness of MSMEs in the digital era, and what are the main challenges faced by MSMEs in accessing legal protection, access to capital, and digital market opportunities?, what are new regulatory models that can be designed to support the strengthening of business laws for MSMEs in the digital era, so that they can increase their competitiveness effectively and sustainably? The research will use an analytical descriptive research method approach to obtain comprehensive results. Primary data was collected through a survey of 100 Business Actors and in-depth interviews with 10-15 selected participants (Consumers). Normative-empirical Legal Approach. Normative approach: ustaka study on the Job Creation Law, ITE Law, Ministerial Regulation related to MSMEs and digitalization, academic literature and legal journals. Empirical approach: Interviews with MSME actors, local governments, MSME Associations, and business law experts. Field observation on MSME digital business practices, and filling out questionnaires. This research shows that there is a discrepancy between the current business law regulations and the real needs of MSMEs in the digital era, especially in North Sulawesi. The applicable regulations have not been able to provide adaptive, inclusive, and applicable legal protection in facing the challenges of digital transformation. Digitized MSMEs face obstacles in the form of legal uncertainty, limited access to regulatory information, and lack of legal support from local governments. To answer these problems, a new regulatory model is needed that is modular, adaptive to technology, and based on sectoral needs. This model must be developed through a participatory approach, which combines legal doctrinal studies with direct input from MSME actors as the main subject. The implementation of this new regulation must also be accompanied by strengthening digital legal literacy and providing access to easy, cheap, and digital-based legal assistance.